Islam and politics: political attitudes of the elites in Muhammadiyah 1998-2010 - Al-Hamdi, Ridho (State Institute of Islamic Studies (STAIN) Salatiga, 2013)
This study examines the roles of political elites in the Muhammadiyah in facingthe dynamics Muslim politics in post New Order regime. There are three issuesdiscussed: the emergence of Islamic political parties, the desire to implementthe Jakarta charter as a state ideology, and the rise of terrorism. The result ofthe study demonstrated that there are four variants of the political attitudes ofthe elites in Muhammadiyah in post-New Order regime: 1) transformative-ideal-istic; 2) moderate-idealistic, 3) realistic-critical, and 4) accommodative-prag-matic. The variations are deeply influenced by two main factors: the sociologicalbackground and organizational factor.Penelitian ini menguji peran elit politik dalam Muhammadiyah dalam menghadapidinamika politik Muslim pada era rezim pasca Orde Baru. Ada tiga isu yangdibahas: munculnya partai-partai politik Islam, keinginan untuk melaksanakanPiagam Jakarta sebagai ideologi negara, dan munculnya terorisme. Hasil penelitianmenunjukkan bahwa ada empat varian sikap politik para elite di Muhammadiyahpada era rezim pasca-Orde Baru: 1) transformatif-idealis; 2) moderat-idealis, 3) realistis-kritis, dan 4) akomodatif-pragmatis. Variasi ini sangat dipengaruhioleh dua faktor utama, yaitu latar belakang sosiologis dan faktor organisasi.